LAW ASPECT OF â€œLET THE PRODUCER AWAREâ€ PRINCIPLES RELATED TO CONSUMER PROTECTION LAW IN INDONESIA - Deviana Yuanitasari; Sonny Dewi; Susilowati Suparto; Hazar Kusmayanti (NOTARIIL Jurnal Kenotariatan, 2019)
Changes in the legal construction begin with a paradigmatic shift in the relationship between the consumer and businesses, as reflected in the preference of let the producer aware principle in favor of letting the buyer aware principle. This study aims to find out the implication of the let the producer aware principle for goods and services, and its development in consumer protection law in Indonesia and to find out the legal system of Indonesia adopts the let the producer aware principle in order to protect Indonesian consumers. The research method applied in this study is normative juridical approach. The data obtained from the study of literature which is used as secondary data. Furthermore, interviews were conducted to obtain primary data, and then the data were analyzed by juridical qualitative method. As a result of analysis, it shows that firstly: the implementation of let the producer aware principle in Indonesia has not been properly conducted because of the common perception that consumersâ€™ opinion is less valuable than producersâ€™. Secondly, the adoption of the let the producer aware principle for consumer protection by Indonesian Legal policy is shown by Law Number 8 Year 1999 about Consumer Protection (Indonesian Consumer Protection Act), which is based on the principle of fault liability, utilizing reversed burden of proof. This way, both parties are protected, because it proportionally distributes the liability to each party. In conclusion, both producers and consumers are equally protected on condition that they can provide evidence of the losses obtained.